Evaluation of Interleukin-10, Vascular Endothelial Growth Factor Levels, and Bone Marrow Parameters in Multiple Myeloma Patients at Diagnosis and After Treatment - Fulya Memis; Meryem Yalvac Kandefer; Sonay Aydin; Klara Dalva; Selami Kocak Toprak (Diagnostics)
Background: Interleukin-10 (IL-10) and vascular endothelial growth factor (VEGF) are believed to possess a role in the pathophysiology of multiple myeloma (MM). We aimed to assess the significance of these parameters in the diagnosis, monitoring, and prognosis of the disease by examining them in patients at diagnosis and post-treatment and comparing the findings with those of healthy individuals. Methods: We conducted blood sampling from 35 patients diagnosed with MM at the time of diagnosis and from 15 of these patients post-treatment. We additionally assessed similar serum markers in a control group of 15 healthy individuals. Furthermore, we documented laboratory results, organ involvement, comorbidities, and CD27-CD81 levels assessed using flow cytometry in the bone marrow, along with treatments and patient responses. We also examined the quantity of cells collected during mobilization in patients who had autologous stem cell transplantation. Results: We found a positive correlation (p = 0.028/p = 0.035) between IL-10 and VEGF with the international staging score. In patients with renal involvement, IL-10 levels were higher and VEGF levels were lower than those without renal involvement (p = 0.011/p = 0.012). We showed that VEGF levels decreased significantly with treatment (p = 0.001). We found no statistically significant correlation between treatment responses and IL-10 and VEGF. The number of CD34 cells collected by mobilization showed a negative correlation with CD27 and a positive correlation with VEGF (p = 0.007/p = 0.032). Conclusions: Serum IL-10 level is associated with ISS and renal involvement in MM patients. There is a positive correlation between serum VEGF levels and the number of stem cells collected during mobilization. As CD27 expression increases, the number of stem cells collected in mobilization decreases.